(untitled) (KASBIT Business Journal, 2021)
Study is done to imprisonment the impact of cash conversion cycle (CCC) on the financial performance of the sector “Food and Personal Care Product” which is listed on Pakistan Stock Exchange. The effect of lathe 1st five years’ performances are captured from 2011-15. The sector comprises of companies but five-year complete data is available for only 14 companies. Panel data analysis is used to determine the results. Eight hypotheses were redeveloped and tested to examine the liquidity position concerning financial performance. Out of four hypotheses related to the dependent variable ROA, one is accepted. The AAP hypothesis showed the same result as this was modeled while AAR, and AI hypotheses are rejected. Again CCC tested with ROA to reconfirm the results of the regression model but the null hypothesis is accepted. Out of four hypotheses related to the dependent variable, ROE two are accepted. The hypothesis of AAR and AI are rejected. While the other two hypotheses related to AAP and CCC are accepted. It is reconfirmed by comparing CCC with the ROE which accepts the alternative hypothesis. The result gave a clear picture about liquidity (CCC) impact which has a negative relationship with the company’s performances if the dependent variable is ROE.